CD4 T Helper Cells Instruct Lymphopenia-Induced Memory-Like CD8 T Cells for Control of Acute LCMV Infection - Schmitt, Michaela E. R.; Sitte, Selina; Voehringer, David (Frontiers in Immunology, 2016)
Lymphopenic conditions lead to expansion of memory-like T cells (TML) which develop from naïve T cells by spontaneous proliferation. TML cells are often increased in the elderly population, AIDS patients and patients recovering from radio- or chemotherapy. At present it is unclear whether TML cells can efficiently respond to foreign antigen and participate in anti-viral immunity. To address this question, we analyzed the immune response during acute low-dose infection with lymphocytic choriomeningitis virus (LCMV-WE) in T cell lymphopenic CD4Cre/R-DTA mice in which most peripheral T cells show a TML phenotype. On day 8 after infection the total number of effector T cells and polyfunctional IFN-gamma and TNF-alpha producing CD8 T cells were 3-5-fold reduced in CD4Cre/R-DTA mice as compared to controls. Viral clearance and the humoral immune response were severely impaired in CD4Cre/R-DTA mice although CTLs efficiently killed transferred target cells in vivo. Transfer of naïve CD4 T cells but not anti-PD-L1 blockade restored the expansion of antigen-specific polyfunctional CD8 T cells and resulted in lower viral titers. This finding indicates that under lymphopenic conditions endogenous CD4 TML cell lack the capacity to promote expansion of CTLs. However, CD8 TML cells retain sufficient functional plasticity to participate in anti-viral immunity in the presence of appropriate help by fully functional CD4 T cells. This capacity might be exploited to develop treatments for improvement of CD8 T cell functions under various clinical settings of lymphopenia.